2018
DOI: 10.1021/acsmacrolett.8b00506
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in Lamellae, Cylinders, and Double Gyroid Block Copolymer Nanostructures

Abstract: We study transport of penetrants through nanoscale morphologies motivated by common block copolymer morphologies, using confined random walks and coarse-grained simulations. Diffusion through randomly oriented grains is 1/3 for cylinder and 2/3 for lamellar morphologies versus an unconstrained (homopolymer) system, as previously understood. Diffusion in the double gyroid structure depends on the volume fraction and is 0.47−0.55 through the minority phase at 30−50 vol % and 0.73−0.80 through the majority at 50−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 82 publications
9
98
0
Order By: Relevance
“…BCC', HEX', GYR'), we assume that = 1. The numerical values of and reported in Table II are taken from refs 30,65 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BCC', HEX', GYR'), we assume that = 1. The numerical values of and reported in Table II are taken from refs 30,65 .…”
Section: Resultsmentioning
confidence: 99%
“…GYR, LAM, and GYR'). Recent computational studies by Shen, Brown, and Hall have shown that the lamellar morphology is optimal for ion diffusion 30 . The purpose of this paper is to experimentally characterize ion transport through different morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism for forming physically crosslinked organogels is employment of an ABA triblock copolymer and a midblock selective solvent. This combination drives self‐assembly via microphase separation of the copolymer endblocks resulting in distinct endblock domains of various sizes and geometries depending on the polymer concentration and block composition 19–23 . Furthermore, the ABA copolymer architecture necessitates that midblocks are tethered to endblock domains at both termini.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Theoretical simulations and experimental results demonstrated that ion conductivity of nanostructured block copolymer electrolytes highly depends on ionic domain continuity and orientations across grain boundaries. [6][7][8][9][10] Among diverse morphologies, the double gyroid phases and inverse hexagonal cylinders with ion-conductive domains as the matrix as proton-conducting channels. [41] Our group utilized POMs as electrostatic crosslinkers to access bicontinuous nanocomposites with enhanced proton conductivity and modulus from lamellar poly(styrene-block-2-vinylpyridine) (PS-b-P2VP).…”
Section: The Primary Issue Of Polymer Electrolytes Is To Achieve Highmentioning
confidence: 99%